Opinions and Needs of Mainstream Classroom Teachers About Classroom Management - Akalin, Selma (Ankara Univ, Fac Educational Sciences, 2015)
Effective mainstreaming in the literature suggests taking into account the students' individual differences and making educational/instructional practices as accepting all students as well as being inclusive. Even though effective classroom and behavior management are very critical especially for teachers who have students with special needs in their classrooms, classroom and behavior management in teacher education has been neglected in teacher education, and this neglect has led to poor education about this topic in undergraduate studies as well as in in-service education programs for teachers. Therefore, it is suggested that mainstream teachers need support for classroom management. The purpose of this study is to examine opinions and needs of elementary mainstream classroom teachers about classroom management. In order to collect data, an interview form was developed that consisted of semi-structured questions to identify opinions, competencies, needs of teachers about mainstreaming practices and about classroom management practices in mainstream classrooms; and in-depth interviews were conducted with six elementary teachers using this form. The finding showed that the mainstream teachers had limitations in knowledge and skills about mainstreaming practices and they had difficulties in classroom management in mainstream classrooms.
Keywords: Mainstreaming/inclusion; classroom management; teachers; semi-structured interview; inductive analysis